SEJARAH MASJID RAYA SULTAN RIAU DI PULAU PENYENGAT KOTA TANJUNG PINANG PROVINSI KEPULAUAN RIAU - Olisstiowati, Cifta Ayu; Ibrahim, Bedriati; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The history of the development of Islam in Indonesia has brought influence to the minds of the people. One of them is the culture of the regions in Indonesia and the Malay Tribe is one of them. The majority of the people are Malay with one of them in Indonesia in the Riau Islands region. Where the development of Islam in this area can be seen from the greatness of the Melayunya Sultanate, the Riau-Lingga Sultanate which stands influenced by the style of culture and Islamic wisdom in this Malay land. One of them can be seen from its historic building, the Great Mosque of Sultan Riau. The research objectives are 1) For the history of the Great Mosque of Sultan Riau on Penyengat Island in Tanjung Pinang City, 2) To find out the function of the Great Mosque of Sultan Riau on Penyengat Island in Tanjung Pinang City, 3) To find out the symbolic meanings of several building parts in Great Mosque of Sultan Riau, 4) To find out tourists' interest in historical tourism in the Great Mosque of Sultan Riau. The research uses qualitative methods with a historical approach with data collection techniques, namely interviews, observation, documentation and decision-making. The results of this study were the Great Mosque of Sultan Riau began to be built around 1803 by Sultan Mahmud Syah III, which was then presented with Penyengat Island to Engku Putri Raja Hamidah Binti Raja Haji Fisabilillah as a Bride. The Great Mosque of Sultan Riau also has a function of a mosque that is different from other mosques because this mosque is one of the mosques which participated in the interests of the Riau-Lingga Sultanate. The Great Mosque of Sultan Riau has a unique and symbolic building form that is rarely owned by other mosques and the attractiveness of this mosque which is able to increase the interest of tourists on Penyengat Island.Key Words: The Great Mosque Of Sultan Riau, Penyengat Island